Analysis of pathogenic bacteria and antimicrobial residues in bovine waste milk on dairy farms in southern Chile - Fernando Ulloa; Fernando Ulloa; Martina Penati; José M. Hernández-Agudelo; José M. Hernández-Agudelo; Carlos Tejeda; Pamela Steuer; María Filippa Addis; Armin Mella; Nivia Canales; Juan Pablo Soto; Miguel Salgado (Frontiers in Veterinary Science)
Waste milk (WM), a byproduct of dairy production, is often used as a cost-effective feed for calves, but it can contain pathogens and antimicrobial residues, which pose health risks. This study examined the microbiological quality and the presence of antimicrobial residues in WM from 36 dairy farms in southern Chile. In a cross-sectional study, WM samples were collected, and farm management data were gathered through a questionnaire. The samples were analyzed for total bacterial load, coliforms, staphylococci, streptococci/streptococci-like organisms (SSLOs), Salmonella spp., Mycobacterium avium subsp. paratuberculosis (MAP), Mycobacterium bovis, Mycoplasma spp., Prototheca spp., methicillin-resistant Staphylococcus aureus (MRSA), and extended-spectrum beta-lactamase (ESBL)-producing E. coli. Antimicrobial residues were detected using a commercial test. A high average bacterial load (7.63 × 106 CFU/mL) and significant levels of staphylococci, SSLOs, and coliform were found. In addition, S. aureus (33.3%), MAP (11.1%), and Salmonella spp. (2.8%) were detected. ESBL-E. coli was found on five farms, with blaCTX-M being the predominant gene. Antimicrobial residues, mainly beta-lactams, were present in 55.6% of samples. These results show that WM in this region frequently contains pathogens, antimicrobial residues, and resistant bacteria. Current farm practices, such as feeding untreated WM to calves, may contribute to the spread of antimicrobial resistance and compromise calf health.